Generation Y medical doctors’ experiences of a positive psychology 2.0 intervention for burnout in a South African public hospital - Oosthuizen, Rudolf M.; Disemelo, Keitumetse; Mayer, Claude-Hélène (Frontiers in Psychology, 2022)
The aim of the research was to explore experiences of a Positive Psychology 2.0 based intervention for burnout amongst Generation Y medical doctors working in the South African public health sector. The emphasis is on the potential benefits and recommended intervention amendments in a specific cultural context of South Africa. There are limited empirically based interventions for burnout, even for at-risk populations, such as newly qualified medical doctors working in the South African public health sector. The newly qualified medical doctors in South Africa are largely within the Generation Y cohort aged between 25 and 35. Burnout affects new qualified Generation Y medical doctor’s private lives, the services they offer and the recipients of their care, yet most research focuses on identifying the risk factors for medical doctors in the South African public health sector, and rarely on potentially effective intervention. A phenomenological approach was used in a collective case study method in three phases, namely: phase I – pre- PP2.0 intervention; phase II – PP2.0 intervention; and phase III – post- PP2.0 intervention. The Maslach Burnout Inventory was applied to quantify the level of burnout. This study offers findings that could be incorporated into a bigger burnout intervention strategy in the South African public health sector involving all stakeholders to ensure that burnout is combatted on a long-term basis. Furthermore, the findings emphasised certain culture-specific structural issues, as well as the impact that neglecting burnout has on newly qualified medical doctors working in the South African public health sector and their patient care. Certain recommendations were made for the South African public health sector for future research in the field of positive psychology, and for facilitators working with burnout amongst newly qualified medical doctors.